Filed trials of an instrumented lifeboat in ice conditions - Simões Ré, A.; Kuczora, A.; Veitch, B. (2008)
Emerging hazards on a ship or offshore petroleum installation can lead to an evacuation scenario. The means of independent evacuation on board must be capable of operating in the conditions that prevail at the time of the emergency. It is essential to know what to expect of evacuation systems in terms of their utility in the range of weather conditions that can reasonably be expected in a given operating region, including the presence of sea ice. It is equally important to account for the interaction of the evacuation systems and the people who have to use them. Peer reviewed: Yes NRC publication: Yes